Surface modification of activated carbon fabric with ozone. Part 2: Thermal analysis with TGA-FTIR and DTA. Issue 6 (2nd June 2016) - Cataldo, Franco; Putz, Mihai V.; Ursini, Ornella; Angelini, Giancarlo
ABSTRACT: Two samples of activated carbon fabrics (ACF) with very high surface area (>1300 to >1800 m 2 /g) fully ozonized in the part 1 of this study were analyzed by thermogravimetric analysis (TGA) coupled both with differential thermal analysis (DTA) and FT-IR spectroscopy (TGA-FTIR). The adsorbed water and the amount of oxygenated functional groups were determined. The ozonized ACF shows an exothermal decomposition at about 181–189°C which may be due at least in part to the decomposition of ozonide and/or peroxide groups. The TGA-FTIR has revealed that the main products released from the thermal decomposition are CO2 followed by CO. Formic acid was detected only in correspondence to the exothermal transition at 181°C and was taken as a proof of the decomposition of secondary ozonides.